Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: \(N=\dfrac{3x^5-4x^4+6x^3}{-2x^2}=-\dfrac{3}{2}x^3+2x^2-3x\)
b: \(N=\dfrac{\left(6x^4y^5-3x^3y^4+\dfrac{1}{2}x^4y^3z\right)}{-\dfrac{1}{3}x^2y^3}=-18x^2y^2+9xy-\dfrac{3}{2}x^2z\)
c: \(\Leftrightarrow N\cdot\left(y-x\right)=\left(x-y\right)^3\)
\(\Leftrightarrow N=\dfrac{\left(x-y\right)^3}{y-x}=-\left(y-x\right)^2\)
d: \(\Leftrightarrow N\cdot\left(y^2-x^2\right)=\left(y^2-x^2\right)^2\)
hay \(N=y^2-x^2\)
a) \(=x^2-2x+3-2x-x^2-2+4x=1\)
b)\(=6x+10x^2-6x+2x=10x^2+2x=2x\left(5x+1\right)\)
c)\(=3x^{n-2}.x^{n+2}-3x^{n-2}.y^{n+2}+y^{n+2}.3x^{n-2}-y^{n+2}.y^{n-2}\)
\(=3x^{2n}-y^{2n}\)
Bài 5.5:
\(\left(2x-3\right)\left(x+1\right)+\left(4x^3-6x^2-6x\right):\left(-2x\right)=18\)
\(\Leftrightarrow\left(2x^2+2x-3x-3\right)+2x\cdot\left(2x^2-3x-3\right):\left(-2x\right)=18\)
\(\Leftrightarrow2x^2-x-3-2x^2+3x+3=18\)
\(\Leftrightarrow2x=18\)
\(\Leftrightarrow x=\dfrac{18}{2}\)
\(\Leftrightarrow x=9\)
a) \(=3x^{n-2}.x^{n+2}-3x^{n-2}.y^{n+2}+y^{n+2}.3x^{n-2}-y^{n+2}.y^{n-2}\)
\(=3x^n-y^n\)
b) ; c) ; d) Tương tự nhé